Antioxidant, Antibacterial and Analgesic Activities of Buddleja asiatica Extract - Karki, Subash; Sapkota, Biswash (Nepal Journal of Health Sciences, 2022)
Introduction: Buddleja asiatica is an upright, evergreen shrub of the Loganiaceae family that can reach up to 1 to 8 meters tall and found between 300-2000 meters height in Nepal.Objectives: The objectives of this study are to assess the antibacterial, antioxidant, and analgesic properties of Buddleja asiatica aerial component.Methods: A typical chemical test was outlined to conduct the phytochemical analysis. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radicals scavenging experiment was used to quantitatively quantify the antioxidant activity of the methanolic extract. By using the well diffusion method, the antibacterial activity was assessed against Escherichia coli and Staphylococcus aureus. Swiss albino mice were utilized to test the analgesic efficacy of the extracts using the acetic acid-induced writhing method and the tail flick method.Results: The phytochemical screening identified the presence of reducing sugars, tannin, phenol, alkaloid, glycoside, and flavonoids. With a zone of inhibition of 19 mm, antibacterial efficacy against Staphylococcus aureus was demonstrated. The extract demonstrated scavenging potential in the DPPH free radical scavenging experiment, with an IC50 value of 123.68 μg/mL. At 600, 800, and 1000 mg/kg, the acetic acid-induced writhing method showed a significant (P < 0.05) analgesic effect. The tail flick approach, which evaluates the pain reaction time, also produced similar results.Conclusion: Different secondary metabolites contained in Buddleja asiatica were found in the methanolic extract, and these secondary metabolites were determined to be physiologically active in terms of good antioxidant, analgesic, and antibacterial activities.